Dietary pattern and health-related quality of life among breast cancer survivors - Na-Hui Kim; Sihan Song; So-Youn Jung; Eunsook Lee; Zisun Kim; Hyeong-Gon Moon; Dong-Young Noh; Jung Eun Lee (BMC, 2018)
Abstract Background There is limited evidence for the association between dietary pattern and quality of life among breast cancer survivors. We examined the association between dietary patterns and health-related quality of life (HRQoL) among Korean breast cancer survivors. Methods Our study included a total of 232 women, aged 21 to 79 years, who had been diagnosed with stage I to III breast cancer and who underwent breast cancer surgery at least 6 months prior to our baseline evaluation. We assessed HRQoL using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) and the Quality of Life Questionnaire Breast Cancer Module 23 (QLQ-BR23). We conducted a factor analysis to identify the major dietary patterns and used a generalized linear model to obtain the least squares mean (LS mean) and 95% confidence interval (CI) for HRQoL according to the dietary pattern scores. Results We identified 2 major dietary patterns: the Healthy dietary pattern and the Western dietary pattern. We found that breast cancer survivors who had higher Healthy dietary pattern scores tended to have lower dyspnea scores but higher insomnia scores, compared to breast cancer survivors with lower Healthy dietary pattern scores. For dyspnea, the LS mean (95% CI) was 8.86 (5.05-15.52) in the bottom quartile and 2.87 (1.62-5.08) in the top quartile (p for trend = 0.005). This association was limited to survivors with stage I for dyspnea or survivors with stage II or III for insomnia. Conclusions Healthy dietary patterns were associated with better scores for dyspnea but worse scores for insomnia among breast cancer survivors. Other components of EORTC QLQ did not vary by dietary patterns overall, but they warrant further investigation for subgroups of breast cancer survivors.